PWE-053 Variation In Adenoma Detection Rate In Bowelscope Screening. (9th June 2014) - Bevan, R; Nickerson, C; Blanks, R; Patnick, J; Loke, R; Saunders, B; Stebbing, J; Tighe, R; Veitch, A; Painter, J; Rees, CJ
Abstract : Introduction: The English Bowel Cancer Screening Programme has been expanded to include a one-off flexible sigmoidoscopy offered to all 55 year olds, called BowelScope Screening. Screening commenced in May 2013, with 6 pilots sites performing flexible sigmoidoscopies in the first 8 months of screening. Methods: The NHS Bowel Cancer Screening System database was interrogated and ADRs reviewed for each screening centre and screening endoscopist. A funnel plot was constructed using the log odds method. Results: 49 endoscopists have performed 4444 sigmoidoscopies at 6 screening centres. Endoscopists had performed 2–330 procedures (median 66, mean 91), 29 endoscopists had performed ≥50 procedures, of these, 17 had performed ≥100 procedures. Overall BowelScope ADR is 8.6%. ADR by centre is shown in Table 1 . Centre 2 has a higher ADR than the other centres. When considering all procedures, this difference reaches statistical significance when compared to centres 3, 5, and 6 (p < 0.05), and approaches significance when compared to centre 1 (p = 0.0687) and centre 4 (p = 0.0548). When considering procedures done by endoscopists who have performed ≥50 or ≥100 sigmoidoscopies, there remains a significant difference (p < 0.05) between centre 2 compared to centres 5 and 6, but not to the other centres. Creating a funnel plot of individual endoscopist ADRs, demonstrates one endoscopist below the 99.8% control limit (Figure 1 ). Conclusion: Adenoma detection rates within BowelScope screening show variation between centres. There is also variation between endoscopists in terms of individual ADRs, although all but 1 endoscopist are above the 99.8% lower control level on funnel plot. These variations require further exploration at both centre and individual level; feedback and education methods will be used to improve ADRs. Consideration should be given to establishing an ADR standard. Disclosure of Interest: None Declared.